Elementos de metadados para a descrição de jurisprudência: uma proposta aplicada em ambientes digitais jurídicos - James, Talita Daemon (2020)
Jurisprudence, as an expression of legal information, is an information resource, with specific characteristics and peculiarities and which needs studies, with regard to the descriptive treatment of information of this nature. It is proposed to investigate, in the available scientific literature, patterns of case law description, in order to identify initiatives, metadata standards, best practices or metadata elements used in the process of representing this resource. It is questioned, what are the appropriate metadata elements to guarantee the efficient recovery of jurisprudence in digital legal environments? The objective is to identify and analyze the adoption of metadata elements and standards for the description of jurisprudence applied to the Brazilian context. Characterized by an exploratory and descriptive methodology, the theoretical and methodological corpus was constructed to understand the metadata elements necessary for the description of jurisprudence, based on the Systematic Literature Review method, which made it possible to identify and outline elements of indispensable metadata applicable to the representation of jurisprudence. As results, 46 metadata elements are presented, which were mapped based on the initiatives, metadata standards, best practices and metadata elements derived from the documentary mass identified in the Systematic Literature Review in the process of describing Brazilian jurisprudence, constituting it is a proposal applied in historical jurisprudence and current jurisprudence. Thus, the proposal of metadata elements for the description of jurisprudence developed in this research can be considered a starting point for the digital legal environments to be better structured, in the effective use of metadata elements for the representation of Brazilian jurisprudence and allowing the interoperability between information systems, providing the necessary conditions for their presentation and retrieval, in the appropriation of information content to the end user.